A Fast and Stable Time Locked Loop for Network Time Synchronization with Parallel FLL and PLL - Andrich, Carsten; Bauer, Julia; Grose, Peter; Ihlow, Alexander; Galdo, Giovanni Del (IEEE International Symposium on Precision Clock Synchronization for Measurement, Control, and Communication, ISPCS, 2018)
We propose a concept for accurate network time synchronization. In comparison to NTPv4 and PTPd, which use a closed-loop design with a single loop filter, our approach splits the task into two fundamental aspects: First, matching the local clock's frequency to the reference frequency is enforced (syntonization). Second, the remaining constant offset between both clocks is minimized (synchronization). We suggest syntonization with a frequency locked loop (FLL) using an open-loop design and synchronization with an additional feedback phase locked loop (PLL). This concept of a time locked loop is advantageous, as it allows faster clock synchronization (smaller settling times) compared to a joint closed-loop design, while furthermore avoiding transient oscillations.
CRIS-Team Scopus Importer:2025-11-10
Keywords: Frequency locked loop (FLL); IEEE 1588; Network time protocol (NTP); Phase locked loop (PLL); Precision time protocol (PTP); Slave clock servo; Time locked loop (TLL)